Knowledge of HIV status and antiretroviral therapy use among sexually transmitted infections service attendees and the case for improving the integration of services in South Africa: A cross sectional study. Issue 39 (September 2018) - Kufa, Tendesayi; Maseko, Venessa D.; Nhlapo, Duduzile; Radebe, Frans; Puren, Adrian; Kularatne, Ranmini S.
Abstract : Abstract: We describe knowledge of human immunodeficiency virus (HIV) status, correct report of HIV status and antiretroviral therapy (ART) use among sexually transmitted infection (STI) service attendees in South Africa. An anonymous questionnaire was administered and serological HIV testing done. Proportions of attendees reporting knowledge of HIV status and HIV status consistent with laboratory results and ART use (among HIV positives) were determined as were factors associated with knowledge and inconsistent report of HIV status. Of 1054 attendees, 288 (27.3%) were HIV positive and 830 (78.8%) self-reported knowledge of HIV status. Not knowing one's HIV status was associated with male gender [adjusted Odds Ratio (aOR) 2.66 (95% confidence interval (CI) 1.70–4.18] medical circumcision [aOR 0.48 (95% CI 0.24–0.95)] and site [Gauteng Province (GP)-aOR 6.20 (95% CI 3.51–10.95), Eastern Cape (EC)-aOR 17.29 (95% CI 10.08– 29.66) versus Free State (FS)/Western Cape (WC) sites]. Of 219 HIV positive attendees with knowledge of HIV status, 136 (62.1%) self-reported being HIV positive, of whom 80 (58.8%) reported taking ARVs in the preceding 3 days. Inconsistent report of status was associated with males [aOR 2.26 (95%CI 1.05–4.87)], prior STI treatment [aOR 0.33 (95% CI 0.16–0.69)], recent HIV testing (6months) [aOR 3.20 (95% CI 1.62–6.36)] and site [GP-aOR 6.89 (95% 3.21–14.82), EC-aOR 5.08 (95% CI 2.15–11.64) versus FS/WC sites]. Knowledge of HIV status was lower than targeted. HIV testing and linkage to care services are essential in STI-related care and validation of self-reported indicators in this population maybe necessary.